Clinical Evaluation of Xylazine-Butorphanol-Guaifenesin-Ketamine as Short-Term TIVA in Equines. (21st April 2011) - Thakur, Bhanu Partap Singh; Sharma, Sandeep Kumar; Sharma, Arvind; Kumar, Adarsh
Abstract : Xylazine (1.1 mg/kg), butorphanol (0.02 mg/kg), guaifenesin 5% (20 mg/kg), and ketamine (2.2 mg/kg) combinations were able to induce short-term surgical anaesthesia for 23.33 ± 2.57 min in Spiti ponies with excellent to good muscle relaxation and analgesia. Urination and neighing was a constant feature during recovery period. Biphasic P wave, biphasic T wave, and depressed PR segment were common electrocardiographic findings. Biochemical attributes were within physiological limits except a significant increase in ALT values during anaesthesia. The values returned to normal during recovery ruling out any renal or hepatic toxicity. Occasionally, negative T wave, notched P wave, and sinus block were noticed. It is recommended that the anaesthetic combinations xylazine-butorphanol-guaifenesin-ketamine can be safely used for short-term total intravenous anaesthesia (TIVA) in equines under field conditions.